"ANALYZING THE IMPACT OF CRUDE OIL PRICES ON ECONOMIC ACTIVITY IN SELECTED OPEC MEMBER COUNTRIES" - Muqdad Zaki Hameed Banana; Mahmoud Hoshmand; Mehdi Behname (Scholars Digest Publishing, 2023)
The impact of crude oil prices on countries' economies has been a subject of interest for decades. During this time, the empirical linkage between oil prices and economic activity has been continuously studied; however, the measured results have shown different and contradictory outcomes. Therefore, the present study aims to examine the effect of crude oil prices on economic activities in selected OPEC member countries from 2000 to 2019. This research employs panel data methodology and a simultaneous equation system approach using a three-stage least squares (3SLS) method. The results indicate a positive and significant impact of crude oil prices on the consumer price index and liquidity volume, amounting to 0.221 and 1.200, respectively. Additionally, the results suggest a negative and significant influence of crude oil prices on the exchange rate and interest rate, with amounts of -0.195 and -0.175, respectively. This study can also serve as useful research for investigating the impact of crude oil prices on economic activity in other countries.
Keywords: crude oil prices, macroeconomic indicators, three-stage least squares, and OPEC member countries.